DEVELOPMENT OF ACMEOLOGICAL COMPETENCE OF FUTURE EDUCATORS IN THE CONDITIONS OF INFORMATION EDUCATION (Scientific journal of the Fergana State University, 2023)
In this article, opinions on the formation of acmeological positions of future teachers in higher education institutions, to increase their activity in the educational process, to awaken a sense of responsibility for their chosen profession, and to develop various reforms in society.